FePt: LaSrFeO4 nanocomposite film prepared by magnetron and pulsed laser co-deposition method. Issue 18 (15th September 2022) - Dai, Xiuhong; Jia, Yanli; Shi, Jian; Guo, Jianxin; Lou, Jianzhong; Liu, Baoting
Abstract: The extensive application of a multifunctional composite film of metal nanoparticles embedded in a dielectric matrix is remarkable. Due to the oxidation susceptibility of atomic iron, it is difficult to directly fabricate embedded Fe nanoparticles in an oxide dielectric matrix with a Fe target. Because La0.5 Sr0.5 FeO3 can be decomposed into LaSrFeO4 and α -Fe, ferromagnetic and optical absorption FePt:LaSrFeO4 composite films were successfully fabricated at room temperature using Pt and La0.5 Sr0.5 FeO3 as targets via magnetron and pulsed laser co-deposition. Further annealing was performed on the FePt:LaSrFeO4 composite films. FePt is chemically disordered face-centered cubic phase (A1 structure) below 600 o C annealing and chemically ordered face-centered tetragonal phase ( L 10 structure) above 600 o C annealing. With increasing the annealing temperature, a redshift of the absorption peak from 256 to 285 nm is seen, which can be attributed to the size growth of the LaSrFeO4 and FePt nanoparticles in the composite films. The strongest absorption peak at around 269 nm for the 600 o C annealed sample can be attributed to the high crystallographic quality and relatively tiny grain size of FePt particles with uniform distribution. FePt:LaSrFeO4 composite films are ferromagnetic and optically absorbent, making them suited for multifunctional applications. Furthermore, magnetron and pulsed laser co-deposition techniques have the potential to produce multiferroic oxides, in which the coupling of different ordering processes e. g. ferroelectricity and ferromagnetism provides the potential for a new breed of multifunctional devices.